PRINSIP SOLIDARITAS DALAM FILSAFAT SOSIAL SEBAGAI KRITIK TERHADAP INDIVIDUALISME JEMAAT KRISTEN - Stella Atalia Runtuwene; Desianti Sappa’; Lisah Yakoba Sayori; Kristina Bura; Rita Ratte (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
The phenomenon of individualism in contemporary Christian congregations has become a serious concern that displaces solidarity values as the foundation of communal life. This study aims to analyze the principle of solidarity in social philosophy as a normative basis for Christian congregational life of mutual burden-bearing, and to evaluate individualistic tendencies in congregational life from social philosophical and theological perspectives. This research employs a library research method with a descriptive-analytical approach. The findings indicate that social philosophy affirms the social nature of human beings who cannot live apart from one another, and solidarity constitutes the primary bond of communal life. Durkheim's theory of solidarity and Paul's exhortation in Galatians 6:2 together construct a solid argument that individualism within Christian communities represents a deviation from both the call of faith and the social nature of humanity. The study concludes that the solidarity principle of social philosophy critically exposes congregational individualism as a form of both spiritual and social regression that urgently requires correction.